Physical Simulation and Monitoring the Deformation and Fracture of Roadway in Coal Mining - Xiaofei Liu; Shuai Yang; Xuhan Ding; Chong Zhang; Xiaoran Wang; Bin Zhou (Advances in Civil Engineering)
Aiming at the large deformation and the dynamic fracture of roadway during the underground excavation or mining, a physical simulation and strain testing system was established, and the deformation process of surrounding body and its inner strain characteristics of the simulated roadway under loading was carried out. Results showed that the inner strain change of the measurement points can be divided into three types: the strain firstly increases and then decreases, the strain slowly increases and then increases sharply, and strain firstly reduces and then increases. The strain starting time is closely related to the failure path and boundary of tested samples. This paper suggested two criteria for determining the instability of roadways, which are a huge and faster increase of strain at the location of the roof and floor with high absolute value, or a small increase with a peak value or irregular fluctuation. This paper provides a new idea for the simulation of roadway instability and is significant in deeper understanding the deformation and destabilization of underground roadway.